A comparative evaluation of nutritional composition and antioxidant properties of six Malaysian edible seaweeds - Chin, Ying Yee; Chang, Kian Aun; Ng, Wei Mei; Eng, Zei Pei; Chew, Lye Yee; Neo, Yun Ping; Yan, See Wan; Wong, Ching Lee; Kong, Kin Weng; Ismail, Amin (Elsevier, 2023)
Agriculture in the 21st century faces challenges in adopting efficient and sustainable production methods to feed the growing population. In this context, seaweed offers greater advantages over terrestrial plants. This study investigated the nutritional composition and antioxidant properties of six edible seaweeds found in Malaysia. The seaweeds studied were brown (Padina australis, Sargassum binderi, Sargassum polycystum), green (Caulerpa racemosa, Caulerpa sertularioides), and red (Garcilaria changgi) seaweeds. The moisture, ash, protein, fat, and total dietary fibre contents of the seaweeds were analysed according to the Association of Official Analytical Chemists methods. Total available carbohydrate content was assessed using the Clegg-anthrone method. Mineral, amino acid, and fatty acid contents were determined through atomic absorption spectroscopy, high-performance liquid chromatography, and gas chromatography methods, respectively. Results revealed that the seaweeds were all high in total dietary fibre (53.96“76.97 g/100 g dried weight, dw) and ash (4.46“18.53 g/100 g dw) whereas their fat (0.05“4.62 g/100 g dw) content was generally low. The brown seaweeds were good sources of calcium. Red seaweed G. changii had the highest content of essential amino acids whereas brown seaweed S. binderi had the highest polyunsaturated fatty acid and lowest saturated fatty acid contents. Fucoxanthin could only be detected in brown seaweeds. Methanolic extracts of seaweeds showed good antioxidant activities measured using 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity (DPPH-RSA), ferric reducing antioxidant power (FRAP), and trolox equivalent antioxidant activity (TEAC) assays. Overall, this study contributed knowledge on underexploited Malaysian seaweeds and proposed them as an alternative source of nutrients for humans to meet food security challenges.